EGG QUALITY OF SELECTED ACEH NATIVE CHICKENS FED ON THE DIETS COMPOSED OF Indigofera sp. MEAL BASED ON FEED FERMENTATION AS PARTLY SUBSTITUTION OF COMMERCIAL DIET - Muhammad Aman Yaman; Zulfan Zulfan (Jurnal Kedokteran Hewan, 2019)
The objective of this study was to determine the effect of  inclusion of  fermented feed consisted  of 15%  Indigofera sp. + 40% rice bran + 25% corn bran + 20% soybean meal as partial substitution of commercial  diet  on the egg quality of  selected Aceh native (SAN) chickens. As many as 48 SAN pullets were used in this study. The study was performed in a completely randomized design, consisted of 4 treatments and 4 replications. Each replication was an experimental unit consisted of three chickens. The results of study indicated that inclusion of up to 15% fermented feed which was composed of 15% Indigofera sp. + 40% rice bran + 25% corn bran + 20% soybean meal as substitution of commercial layer diet significantly (P0.01) improved yolk index without adverse effect on albumen and eggshell quality of  SAN chickens. As conclution, substitution of fermented feed contained 15% indigofera may improve the egg quality of SAN chickens.